Meta Analysis: Efektifitas Problem Based Learning dalam Meningkatkan Kemampuan Berpikir Kritis Siswa SD dalam Pembelajaran IPA - Anak Agung Sagung Krisna Darmawati; I Nyoman Tika; Putu Artawan; I Wayan Redhana (Jurnal Penelitian Pendidikan IPA, 2025)
The implementation of science learning in schools must be designed to provide a means for students to deepen their understanding of themselves and the natural world or their surroundings. However, in practice, several obstacles or difficulties are encountered, including the lack of facilities and teachers' skills. This research aims to analyze the effectiveness of the implementation of Problem-Based Learning (PBL) in improving the critical thinking skills of elementary school students in science education through a meta-analysis method. This method was conducted on nine journals resulting from quasi-experimental research published between 2021 and 2025. Problem-Based Learning (PBL) has been extensively studied as a learning model believed to be effective in enhancing students' critical thinking skills. The journals were selected based on specific inclusion criteria and analyzed using the RevMan 5.4.1 software to measure effect size. The analysis results show that the implementation of PBL significantly improves students' critical thinking skills, indicated by an overall effect value (P < 0.00001). There is variation in results among the analyzed journals, with effect sizes generally ranging from high to very high. These findings support that PBL can be an effective alternative for teachers in developing students' critical thinking skills, especially in science subjects which are abstract in nature and require problem-solving. The application of PBL is also recommended to be developed at higher education levels.